2008
DOI: 10.1016/j.neuroimage.2008.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Stereotaxic probabilistic maps of the magnocellular cell groups in human basal forebrain

Abstract: The basal forebrain contains several interdigitating anatomical structures, including the diagonal band of Broca, the basal nucleus of Meynert, the ventral striatum, and also cell groups underneath the globus pallidus that bridge the centromedial amygdala to the bed nucleus of the stria terminalis. Among the cell populations, the magnocellular, cholinergic corticopetal projection neurons have received particular attention due to their loss in Alzheimer's disease. In MRI images, the precise delineation of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
314
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 335 publications
(366 citation statements)
references
References 87 publications
15
314
1
Order By: Relevance
“…The sgACC region we identified as responding exclusively to prosocial PEs overlapped with a septal-anterior hypothalamic area that is part of the basal forebrain (43). Recent studies of sgACC function have found signals in this region relevant for social cognition and behavior including credit assignment (44), prosocial and moral behavior (6,16,45,46), the experience of positive affect (47), trust (48), social emotion (49), and vicarious reward (50,51).…”
Section: Discussionmentioning
confidence: 92%
“…The sgACC region we identified as responding exclusively to prosocial PEs overlapped with a septal-anterior hypothalamic area that is part of the basal forebrain (43). Recent studies of sgACC function have found signals in this region relevant for social cognition and behavior including credit assignment (44), prosocial and moral behavior (6,16,45,46), the experience of positive affect (47), trust (48), social emotion (49), and vicarious reward (50,51).…”
Section: Discussionmentioning
confidence: 92%
“…1999; Zaborszky et al. 2008). Both parts of the TMT, especially Part A, require visual search (Crowe 1998).…”
Section: Discussionmentioning
confidence: 99%
“…For a detailed description of the creation of the probabilistic map, we refer to Zaborszky et al. (2008). Ten brains of body donors with no record of neurological or psychiatric disease (five female, age range 37–75 years) were obtained at autopsy and fixed in formaldehyde or Bodian fixative.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The small volume and irregular border has impeded research of the BNM. Extant imaging studies have focused on volume changes in the BNM in association with MCI (Hanyu et al, 2002;Zaborszky et al, 2008;Grothe et al, 2012) with reduced volume extending into the whole BFCS in patient with AD (George et al, 2011;Grothe et al, 2013Grothe et al, , 2014, as compared with healthy aging (Kilimann et al, 2014). For instance, volume reduction of the BNM and temporal lobe structures was associated with impairment in delayed recall in MCI patients (Grothe et al, 2010).…”
Section: Introductionmentioning
confidence: 99%